The Measurement of the Medical Personnel Emotional Condition In Relation to Service Performance - Widhiastuti, Hardani; Kurniawan, Andi; Nurhayati, Titik; Kurniawan, Yudi (Universitas Muria Kudus, 2024)
This study emphasizes on the service performance of medical personnel in hospitals, one of which is due to the emotional condition of the services of the medical personnel. The research method used is quantitative method related to the emotional condition of the medical personnel measured using Vital Sign. The research subjects consisted of 67 medical personnel, but only 50 returned the google forms. While the relationship between the two used SPSS version 22. The validity test showed that the service performance variable was appropriate or valid variable.The result of the statistical analysis of Non Parametric correlation shows that there is relationship with the result of the normality test of p (sig) 0.01. It is proven that the Service Performance variable is not normal, so the test must use the non-parametric correlation test with Spearman-Rho with the correlation coefficient result of 0.562 with p (sig) 0.000. This means that there is significant relationship between the Emotional Condition variable and the Service Performance variable of the medical personnel. The results of this study prove that when the emotional condition of medical personnel increases, the service performance will decrease, which means that the responsibility for service quality decreases somewhat, dares to take risks for services that are slightly neglected, has service goal that is somewhat less attention, less planning for services, less thinking about feedback from the services provided, and the possibility of less thinking about getting the opportunity to realize services.Penelitian ini menekankan pada kinerja pelayanan tenaga medis di rumah sakit yang salah satunya disebabkan oleh kondisi emosional terhadap pelayanan tenaga medis tersebut. Metode penelitian yang digunakan adalah metode kuantitatif yang berkaitan dengan kondisi emosional tenaga medis yang diukur dengan menggunakan Vital Sign. Subjek penelitian terdiri dari 67 tenaga medis, namun yang mengembalikan google form hanya 50 orang. Sedangkan untuk hubungan keduanya menggunakan SPSS versi 22. Uji validitas menunjukkan bahwa variabel kinerja pelayanan merupakan variabel yang tepat atau valid. Hasil analisis statistik korelasi Non Parametrik menunjukkan adanya hubungan dengan hasil uji normalitas p (sig) 0,01. Hal ini terbukti bahwa variabel Kinerja Pelayanan tidak normal, sehingga pengujian harus menggunakan uji korelasi non parametrik dengan Spearman-Rho dengan hasil koefisien korelasi sebesar 0,562 dengan p (sig) 0,000. Hal ini berarti terdapat hubungan yang signifikan antara variabel Kondisi Emosional dengan variabel Kinerja Pelayanan Tenaga Medis. Hasil penelitian ini membuktikan bahwa ketika kondisi emosional tenaga medis meningkat maka kinerja pelayanannya akan menurun yang berarti tanggung jawab terhadap mutu pelayanan agak menurun, keberanian mengambil risiko terhadap pelayanan agak kurang diperhatikan, tujuan pelayanan yang agak kurang diperhatikan, kurang merencanakan pelayanan, kurang memikirkan umpan balik dari pelayanan yang diberikan, dan kemungkinan kurang memikirkan untuk mendapatkan kesempatan dalam merealisasikan pelayanan.